KEPATUHAN PEMBATASAN CAIRAN PADA PASIEN GAGAL GINJAL KRONIS YANG SEDANG MENJALANI HEMODIALISIS: COMPLIANCE WITH FLUID RESTRICTIONS IN CHRONIC RENAL FAILURE PATIENTS UNDERGOING HEMODIALYSIS - Ningsih, Zakiyah Resha; Saputra, Bayu; Indra, Rani Lisa (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2024)
Introduction: Hemodialysis is the most widely used kidney replacement method. One of the interventions used is limiting fluid intake, because excessive fluid intake can cause complications, thereby increasing high morbidity and mortality rates. This study aimed to determine the description of compliance with fluid restrictions and compliance with fluid restrictions based on characteristics in patients with chronic renal failure who are undergoing hemodialysis. Methods: The type of research used was quantitative with a descriptive design using a survey approach with a sample of 54 people using univariate analysis. Result: The characteristics of the respondents were that the majority were early elderly (46-55) years old, female gender, high school education, duration of hemodialysis > 12 months, and IDWG weight in the heavy category. The results of patient compliance levels were found to be 28 (51.9%) respondents in the less compliant category. Conclusion: Not all respondents want to follow the recommendation to comply with fluid restrictions.     Keywords: Chronic renal failure; Hemodialysis; Compliance with fluid restrictions